1981
DOI: 10.1007/bf00990303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of day length and light intensity on 2-tridecanone levels and resistance inLycopersicon hirsutum f.glabratum toManduca sexta

Abstract: First instarManduca sexta (L.) larvae confined on foliage fromLycopersicon hirsutum f.glabratum (accession PI 134417) plants grown under a long-day regime exhibited greater mortality than larvae on foliage from plants grown under a short-day regime. 2-Tridecanone, a toxin important in the insect resistance of PI 134417, was significantly more abundant in the foliage of plants grown under the long-than the short-day regimes. Light intensity influenced neither 2-tridecanone levels nor the expression of resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
2
6

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 11 publications
3
48
2
6
Order By: Relevance
“…The greater feeding damage to unshaded plants could be due to higher G. boliviana abundance on unshaded tropical soda apple plants (Table 1) and/or the adaptation of G. boliviana to tropical soda apple plant defenses. For instance, defensive trichomes on tropical soda apple are larger and denser on unshaded plants (Diaz et al 2011), similar to other solanaceous plants (Kennedy et al 1981;Franca & Tingey 1994). These defensive trichomes are detrimental to most phytophagous insects; however, to G. boliviana larvae, trichomes are essential structures that must be present for a plant to be a suitable host (Gandolfo 2000).…”
Section: Influence Of Sun and Shade Conditions Onmentioning
confidence: 61%
“…The greater feeding damage to unshaded plants could be due to higher G. boliviana abundance on unshaded tropical soda apple plants (Table 1) and/or the adaptation of G. boliviana to tropical soda apple plant defenses. For instance, defensive trichomes on tropical soda apple are larger and denser on unshaded plants (Diaz et al 2011), similar to other solanaceous plants (Kennedy et al 1981;Franca & Tingey 1994). These defensive trichomes are detrimental to most phytophagous insects; however, to G. boliviana larvae, trichomes are essential structures that must be present for a plant to be a suitable host (Gandolfo 2000).…”
Section: Influence Of Sun and Shade Conditions Onmentioning
confidence: 61%
“…Firstly, the exudate production of plants within a particular accession may be variable both in time and space; several authors have shown the strong influence of external conditions, such as daylength and light intensity, on 2-tridecanone levels ( Kennedy et al, 1981 ) and trichome density ( Good and Snyder, 1985). Secondly, the variation in exudate production between accessions may be relevant for breeding varieties better adapted to biological control.…”
Section: Resultsmentioning
confidence: 99%
“…Por exemplo, as espécies de tomate silvestre, similares às cultivadas, conservam os genes envolvidos na biossíntese de potentes defesas químicas que lhes conferem resistência a uma grande variedade de insetos. Lycopersicon hirsutum f. glabratum tem sido classificado como altamente resistente ao ataque de numerosos insetos, entre eles Tuta absoluta (Saravia et al, 1984;Gray et al, 1999), Manduca sexta (Kennedy et al, 1981;Fery & Kennedy, 1987), Phtorimaea operculella, Spodoptera exigua e Heliothis armigera (Juvik & Stevens, 1982).…”
Section: Introductionunclassified